WORKBOOK AS A TOOL OF REPRODUCING METHOD FOR TEACHING MATHEMATICS AT THE UNIVERSITY LEVEL - Shuda, Irina; Оdarchenko, Nataliia (Proceedings of National Aviation University (archive), 2015)
The article highlights the main challenges to be solved in higher education in the modern conditions. It is shown that the implementation of these tasks is possible with the systematic inclusion of the elements of students’ independent work in the teaching process. We established that one of the forms of independent work in the classes and outside teaching hours of higher mathematics discipline is the workbook. Its application allows to teach undergraduate students during the first years to acquire the knowledge independently, to actively analyse, to learn and to transform them for solving the uncommon problems. Authors discuss the workbook for the section "Integral calculus" as an example.